2005
DOI: 10.1016/j.biomaterials.2004.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Self-gelling hydrogels based on oppositely charged dextran microspheres

Abstract: This paper presents a novel self-gelling hydrogel potentially suitable for controlled drug delivery and tissue engineering. The macroscopic gels are obtained by mixing dispersions of oppositely charged crosslinked dextran microspheres. These microspheres in turn were prepared by crosslinking of dextran derivatized with hydroxyethyl methacrylate emulsified in an aqueous poly(ethylene glycol) solution. Negatively or positively charged microspheres were obtained by addition of methacrylic acid (MAA) or dimethylam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
125
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(128 citation statements)
references
References 31 publications
1
125
2
Order By: Relevance
“…as a result of exposure to organic solvent or crosslinking agents, can be avoided when making use of selfassembling systems [13]. In situ formation of hydrogels, mainly based on physical crosslinking between polymer chains can be accomplished through, among others, hydrogen bonding [14,15], crystallization [16], hydrophobic interactions as a result of temperature changes [17], ionic interactions [18][19][20], or stereocomplexes [21,22]. Besides in the protein delivery field, hydrogels have been widely used in tissue engineering applications [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…as a result of exposure to organic solvent or crosslinking agents, can be avoided when making use of selfassembling systems [13]. In situ formation of hydrogels, mainly based on physical crosslinking between polymer chains can be accomplished through, among others, hydrogen bonding [14,15], crystallization [16], hydrophobic interactions as a result of temperature changes [17], ionic interactions [18][19][20], or stereocomplexes [21,22]. Besides in the protein delivery field, hydrogels have been widely used in tissue engineering applications [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of a short peptide (Arg-Gly-Asp) as a target ligand to these micelles improved their cell uptake efficacy [315]. Moreover, dextran (Dex) based microgels e.g., dextran-hydroxyethyl methacrylate (Dex-HEMA) could easily be loaded with macromolecules such as proteins and dyes (FITC) as well as latex nanoparticles (NPs, 20kDa) labeled with dyes [316][317][318][319]. The bio-polycation i.e., a poly-Larginine (pARG) labeled with rodamine B isothiocyanate (RITC) or tertramethylrodamine isothiocyanate (TRITC) can form coatings on the Dex-HEMA microgel yielding a clear red fluorescence [320,321].…”
Section: Polymer Micelles and Capsules Loaded With Fluorescent Therapmentioning
confidence: 99%
“…For example, Hennink et al reported on self-gelling hydrogels based on oppositely charged dextran microspheres (Tomme et al, 2005). These charged dextranmicrospheres were prepared by radical polymerization of hydroxyethyl methacrylatederivatized dextran (dex-HEMA) with methacrylic acid (MAA) or dimethylaminoethyl methacrylate (DMAEMA).…”
Section: Ionic Interactionmentioning
confidence: 99%